OPTIMIZATION OF POKDARWIS COMMUNICATIONS TO INCREASE VISITORS' INTEREST IN PLUNTURAN CULTURAL TOURISM VILLAGE PULUNG DISTRICT, PONOROGO REGENCY - Widiyatmo Ekoputro; Lukman Hakim (Jurnal Scientia, 2023)
At present, people in several villages in Indonesia are trying to provide alternative recreation and entertainment options as cheap and affordable tourist destinations . The tourism village object seeks to promise comfort and is environmentally friendly so that it requires the ability to manage and manage it in such a way that it can become a source of income and income for the village. Plunuran Village , Ponorogo Regency is part of a new tourist destination that requires concrete efforts to introduce this strategy to the wider community and become part of the Pokdarwis to be able to optimize it, so a general definition is needed regarding both elaborating and improving communication strategies . Communication strategy is essentially how to plan ideas ( planning ), delivery of messages ( massage ) and the accuracy of the targetthrough a combination of elementscommunication such as frequency, formality, content and communication channels so that the message conveyed is easily received and understood and can change attitudes or behavior in accordance with the purpose of communication, and this can be very broad depending on the interests within a particular community . Meanwhile, when talking about optimization , the end is how to come up with the best creative ideas in carrying out an effective and efficient activity with optimal results to be able to generate interest in visiting destinations in the Plunuran tourist village as a new tourist destination . Pokdarwis Plunuran village as a communication driver is expected to be able to attract visitor interest. Communication is an important element in carrying out the process of communicating to others so that the desired goals and objectives can be achieved. Efforts to attract visitors to attend the locationin a tourist village is a concrete way to package, manage, present and promise information that can be received and understood by the community. Because effective communication will occur if the message conveyed by the information provider (communicator) to the recipient of the message (communicant) in this case the visitor community does not cause misunderstandings (mis perceptions). Plunuran Village, Pulung sub-district, Ponorogo Regency as a research location is a special attraction for research because the potential of a cultural tourism village fulfills the requirements for research objects, especially the lives of its people who always get along in harmony and are attached to the arts, have a place to perform as well as a schedule for performances, culinary unique and different from other villages, beautiful natural scenery. These potentials and efforts should always be developed together and Pokdarwis can optimally mobilize all potentials so that the village's economy can increase which hopes that the results will be directly proportional to the welfare of the community.